HUBUNGAN ASUPAN NATRIUM DENGAN KEJADIAN HIPERTENSI DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI TAHUN 2014 - enita wahyuni nasution; Mhd.Arifin Siregar; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The excessive sodium intake can increase the blood pressure. Intake sodium will be directly absorbed into blood vessels. This causes sodium level in the blood increases. Sodium has water holding trait, that cause the blood volume increase. Consuming of high sodium continuously causes hypertension. The purpose of this study is to know the relationship of sodium intake with hypertension in UPT Pelayanan Sosial Lanjut Usia Binjai years 2014. Types of research using a cross-sectional study design. Total population as many as 180 of elderly and uses as a sample 0f 63 elderly. The sampling technique with purposive sampling. Measurements on the incidence of hypertension using a sphygmomanometer is done by nurses. The collecting of data on food consumption of the elderly in panti werdha obtained by food weighing and recording food from outside the panti werdha using a recall. The content of sodium in diet was analyzes using software nutrisurvey. The relationship of sodium intake with the occurrence of hypertension was analyzed by Chi-square test. The results of this study show that sodium intake into more sufficient category (66.7%) did not suffer hypertension and sodium intake into over category (70%) suffer hypertension, and obtained p=0,005 means there is significant relationship between sodium intake with the occurrence of hypertension in the elderly in UPT Pelayanan Sosial Lanjut Usia Binjai years 2014. From the results of this research suggested nutritionist to more better maintain and supervise the food consumed elderly. It suggested for elderly to limit salt intake and reducing the sodium content of foods high in order to keep blood pressure normal. Keywords: Sodium Intake, Hypertension, Elderly